2013
DOI: 10.1007/s10522-013-9437-4
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents the development of the metabolic syndrome in male rats exposed to different light/dark regimens

Abstract: Effect of light regimens (standard 12:12 light/dark, constant light, natural lightning of the north-west of Russia) and that of melatonin on the development of metabolic syndrome during aging of rats was studied. It was found out that during the process of aging of rats kept in the conditions of the broken rhythm of day and night, different disturbances of metabolism in the form of abdominal obesity, hyperinsulinemia, hypercholesterolemia, hyperglycemia, hyperbetalipoproteinemia and glycosuria occurred. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 33 publications
0
24
0
1
Order By: Relevance
“…Production of melatonin is permitted at darkness but inhibited by light at night, so night work can inhibit the secretion of melatonin. Animal studies showed that the decreased secretion of melatonin was associated with the abnormalities of metabolic syndrome components (27), whereas artificial supply of melatonin can prevent the development of MetS in rats (28,29). Mirick et al reported that night shift workers had a substantially lower urine level of 6-sulfatoxymelationin and a lower level of cortisol secretion (30).…”
Section: Discussionmentioning
confidence: 99%
“…Production of melatonin is permitted at darkness but inhibited by light at night, so night work can inhibit the secretion of melatonin. Animal studies showed that the decreased secretion of melatonin was associated with the abnormalities of metabolic syndrome components (27), whereas artificial supply of melatonin can prevent the development of MetS in rats (28,29). Mirick et al reported that night shift workers had a substantially lower urine level of 6-sulfatoxymelationin and a lower level of cortisol secretion (30).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the effect of melatonin supplementation on immune function varied highlights the complexity of the underlying relationships between light, melatonin and life history traits. It also suggests that, regardless of taxa, caution should be exercised when making general inferences about the benefits of melatonin based on single trait assays because the relationship between melatonin concentration and immune function (for example) may not be comparable or indeed indicative of the relationship between melatonin and survival [82,93]. It is highly conceivable that, despite its ubiquity, species-level differences in life history and ontogeny will determine the relative importance of melatonin for circadian rhythm or immune function in varying lighting conditions (see also, [97]).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Japanese quail (Coturnix coturnix japonica) immune function was significantly lowered when birds were kept under constant illumination compared with birds maintained on either short-(8 h light) or long-day (16 h light) cycles, but supplementation with melatonin in the drinking water provided a positive dose-dependent immune-enhancing effect [81]. Using a comparable experimental design Vinogradova and Anisimov [82] found that melatonin provided in the drinking water was able to reduce the severity of a number of age-related metabolic disorders in rats exposed to constant illumination. Several major gaps are apparent in the literature.…”
Section: (I) Lan Circulating Melatonin Concentrations and Shifts In mentioning
confidence: 99%
“…Melatonin, a hormone, which is sold as a non-prescription sleeping pill, increases life span and decreases cancer incidence in animals in some studies [226229]. Yet, other studies were inconclusive.…”
Section: Melatoninmentioning
confidence: 99%